2021
DOI: 10.1007/s13205-021-02720-z
|View full text |Cite
|
Sign up to set email alerts
|

Scenedesmus acutus extracellular polysaccharides produced under increased concentration of sulphur and phosphorus exhibited enhanced proliferation of peripheral blood mononuclear cells

Abstract: Exopolysaccharides (EPS) isolated from microalgae are promising immune cell proliferation agents, that could be potentially used as immunostimulants. In the current study, Scenedesmus acutus ( S. acutus ) was grown under varying nutrient (sulphur and phosphorus) concentrations to enhance the EPS production, and the isolated EPS were assessed for their effect on cell proliferation using peripheral blood mononuclear cells (PBMC). Five different concentrations of MgSO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…And one molecule of synthesized glutamate continues to participate in the absorption. e other is used to synthesize nitrogen-containing organics in cells such as proteins and nucleic acids [18], as shown in Figure 1. In the GS/GOGAT cycle, the catalytic reaction of GS is…”
Section: The Effect Of Nitrogen and Phosphorusmentioning
confidence: 99%
“…And one molecule of synthesized glutamate continues to participate in the absorption. e other is used to synthesize nitrogen-containing organics in cells such as proteins and nucleic acids [18], as shown in Figure 1. In the GS/GOGAT cycle, the catalytic reaction of GS is…”
Section: The Effect Of Nitrogen and Phosphorusmentioning
confidence: 99%
“…In contrast, supernatants mainly showed bands associated with different types of carbohydrates but also the presence of proteins, lipids, and nucleic acids (Figures b, b; Table ). In agreement, it has been reported that microalgae’s main extracellular components are exopolysaccharides (EPS), proteins, and small quantities of fatty acids, nucleic acids, and amino acids. , Production of EPS has been reported as a species-dependent process regulated by growth conditions such as concentration of nitrogen and phosphorus. ,, Excreted proteins function as structural components for EPS stabilization and enzymes involved in EPS degradation, C-capture, and protein degradation, among others. , …”
Section: Discussionmentioning
confidence: 64%
“…EPS represent carbon and energy reserves for cells and are often excreted by microalgae as part of physiological processes or under stress conditions [12,21,[26][27][28], such as light intensity and light continuity, temperature [29,30], pH [31,32], excess, limitation or absence of nutrients, such as carbon, nitrogen, phosphorus, sulfur, sodium, potassium, iron, magnesium and calcium [14,33,34], and toxic substances [35,36], such as cadmium [37], copper, lead, chromium, nickel [31,38], and silver [39].…”
Section: Potentiality Of Microalgal Polysaccharides In Bioflocculationmentioning
confidence: 99%